A symphonialis Soul to Understand Oneself and the World. Hildegard of Bingen between Sound and Word (Doctor Virtualis, 2024)
Hildegard of Bingen interprets the whole of human life in terms of harmony and symphony: while harmony means the restoration of the relationship between humans and God and the entire redemption's experience, the present human existence with its dangers, contradictions, and sins, corresponds to a symphony. Hildegard offers a unified vision of human beings, divine for the soul and earthly for the body. Every person is a microcosm, a multiplicity brought back to unity. The human soul is symphonialis, a characteristic expressing both the agreement between soul and body and the participation in every symphony of creation under the relationship that a person has with his or her surroundings, as well as making music.
Keywords: Hildegard of Bingen; vison; harmony; symphony